PERLINDUNGAN HUKUM TRANSAKSI JUAL BELI KOMPUTER RAKITAN MENURUT UNDANG-UNDANG TENTANG PERLINDUNGAN KONSUMEN (Studi Di Bintan Risky Computer Surabaya) - Erie Hariyanto (Faculty of Law, Universitas Jenderal Soedirman, 2012)
In the computer trade is known two terms of the computer type namely Branded computer, which is usually sold in a well packet, assembled by the producer (company) and the second one is assembly computer that nowadays dominates more than 60 % of computer market share in Indonesia in which the trade transaction makes many obstacles which need the solution and law protection for those involved in the trade transaction of assembly computer. By being prevailed the law of number 8, 1999 about consumer protection, it is wondered whether it has given the law protection for those who are involved especially the consumers. It can be devided into three stages, they are preliminary transaction or the bargain of assembly computer through advertisement, the transaction or agreement of the assembly computer trade and the last is the transaction of sale after service that also concerns with the guarantee. The form of lawsuit solution is commonly done by the familial relathionship between the consumer and the seller. It is the best and effective solution, although the law of the consumer protection also gives the place to complain their cases through the consumer lawsuit affairs. Key words: law protection, trade transaction, assembly computer